(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Pregnancy is a special moment in women’s lives, and it is characterized by physical, hormonal and psychological changes. Women’s pregnancy represents an opportunity to promote oral health, however, there are still myths and lacking knowledge on dental treatment during pregnancy. Objective: To evaluate a group of dentists’ level of knowledge on dental care during pregnancy and in HIV-positive pregnant women. Methods: The method adopted in this study includes: prospective, cross-sectional and exploratory quantitative. The study conducted a survey using a questionnaire on the most suitable quarter for dental care, appropriate period of the day for its conduction, appropriate indications for local anesthetic, analgesic and antibiotic, treatments can be performed, and performing XRs. The knowledge regarding HIV-positive pregnant women, the means of vertical transmission of HIV and the type of delivery that pregnant women can perform were also evaluated. Results: The sample consisted of 99 dentists, most of whom were female (74.7%) and with more than 15 years of practice. The vast majority of respondents (79.8%) said they felt confident caring for pregnant patients; with respect to recommended local anesthetic, analgesic, antibiotic and procedures, the results supported the broad literature. However, relation to the most suitable period of the day for dental caring, some aspects of the health of HIV-positive pregnant women and vertical transmission, the professionals’ knowledge did not correspond to that recommended by the literature. Conclusion: The sample of the present study, for the most part, demonstrated knowledge about dental care performed on pregnant women.